Stability, structures, and chaos in nonlinear synchronization networks - Afraimovich, V.S (World Scientific, 1994)
Includes bibliographical references (p. 237-246); 12 parts: Basic Models; dynamics of a Chain of Phase Lock-loop systems with Unidirectional coupling; effect of Inertia of elements on the Dynamics of a flow chain;...